If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -39 = 17 Reorder the terms: -39 + 2x = 17 Solving -39 + 2x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '39' to each side of the equation. -39 + 39 + 2x = 17 + 39 Combine like terms: -39 + 39 = 0 0 + 2x = 17 + 39 2x = 17 + 39 Combine like terms: 17 + 39 = 56 2x = 56 Divide each side by '2'. x = 28 Simplifying x = 28
| 4p+15+33=6p | | -(-8)+4=2(x)+-8 | | 15w-49+33=13w | | -8/3x=16/3 | | 49x+43=48x+45 | | z-32.56=12 | | -12x-14=-86 | | 2z+47=6z-16 | | 2(12y-11)=-4(1-6y) | | -(x-8)+4=2(12)+x | | 25=10+5j | | 5m^2+26m+5=0 | | 2x-3*-13=9 | | -(x-8)+4=2(-12)+x | | 7x+3(5-3x)=5 | | b+3+b=b+50 | | ly-8l+6=15 | | 3a+1=a+19 | | 15.08+w=30.08 | | Cosx/cos^2(2x) | | -5x-3*-13=30 | | 7m+48=8(m+7) | | 3b^2+11b+8=0 | | -5x-(3*-13)=30 | | 18=5-2+6x-x | | -(x-8)+4=2(7)+x | | x+14=35 | | (r-p)/(x-q)=m | | -5x-(-3*-13)=30 | | 2x-4-6=0 | | 12+[6+(13-7)]2-5= | | 72/4.8=20.4/c |